Don Francisco Requena y Herrera: una figura clave en la Demarcación de los Límites Hispano-Lusos en la cuenca del Amazonas (s. XVIII) - Río Sadornil, José Luis del (Revista Complutense de Historia de América, 2003)
The person of Francisco Requena y Herrera is projected as an engineer and as a warlike, emphasizing his labour in Southern America where he built several fortresses and official buildings; he improved the town-planning of Guayaquil village and he took part as a main character of the Spanish side in the 4th Demarcation’s Party of Hispano-Lusitan Border’s Limits in the Amazon Basin.In the name of Requena and in his honour, Requena del Tapiche was established, today the capital of the province of Requena in the Department of Loreto, Perú.